2008
DOI: 10.1016/j.exer.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for generating corneal haze in anterior stroma of the mouse eye with the excimer laser

Abstract: Refractive surgery is a popular method used to reduce or eliminate dependence on glasses and contact lenses. Corneal haze is one of the common complications observed after photorefractive keratectmomy (PRK). The objective of this study was to develop an in vivo mouse model that consistently produces moderate to severe corneal haze in the anterior stroma of the mouse cornea after excimer laser treatment to study myofibroblast biology and corneal wound healing in a genetically defined model. Regular-or irregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 30 publications
3
52
0
4
Order By: Relevance
“…An earlier study found stromal haze to be produced in mouse corneas when BM was disrupted, leaving an irregular surface. 26 The current data confirm these results, showing that the haze accompanies a long-lasting change in stromal ECM organization. A significant increase in corneal light scatter was observed only when BM was disrupted (Figs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An earlier study found stromal haze to be produced in mouse corneas when BM was disrupted, leaving an irregular surface. 26 The current data confirm these results, showing that the haze accompanies a long-lasting change in stromal ECM organization. A significant increase in corneal light scatter was observed only when BM was disrupted (Figs.…”
Section: Discussionsupporting
confidence: 80%
“…25 Epithelial debridement leaving the BM intact reportedly leaves the cornea transparent, whereas disruption of the epithelial BM, particularly one that generates a rough surface on the stroma, heals with anterior stromal haze. 26 The status of the ECM after healing of these two wound types has not been evaluated. The present authors compared the two wound types using a manual procedure for epithelial removal that left the BM intact, as well as a deeper debridement procedure that removed epithelium, BM, and a small portion of anterior stroma.…”
Section: Corneal Woundingmentioning
confidence: 99%
“…The situation can be summarized as ''the physics works,'' but the biological generation of complications and deviations from the correction are still in need of improvement. While much is known about the cellular and molecular biology of corneal wound healing, [1][2][3][4][5][6] improvements beyond this basal knowledge are constantly sought in order to explain the observed variance in optical and refractive outcomes following SA-based surgeries.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were rehydrated and washed 3 times in PBS. The slides were then incubated in 5-bromo-4-chloro-3-indolyl-beta-D-galactopyranoside (X-Gal) staining solution (2 mM MgCl 2 ; Sigma-Aldrich); 5 mM K 4 (CN) 6 -3H 2 O (Sigma-Aldrich); 5 mM K 3 (CN) 6 (Sigma-Aldrich); 1 mg/mL X-Gal (Promega, Madison, WI), in PBS pH 7.4 at 378C in a humidified chamber overnight. The slides were then washed 3 times with PBS, counterstained with nuclear fast red (Vector Labs, Burlingame, CA).…”
Section: Cell Tracing Experimentsmentioning
confidence: 99%
“…The procedures for the induction of corneal angiogenesis were performed on animals under dissociative anesthesia 18 . Antisepsis was performed, and proxymetacaine eye drops (Alcon, Sao Paulo, Brazil) were instilled to promote desensitization of the ocular surface.…”
Section: Animals and Procedures For Alkaline Cauterizationmentioning
confidence: 99%